Pengaruh Kepemimpinan, Sanksi dan Kompensasi yang Dimediasi Motivasi Kerja Terhadap Disiplin Kerja Pegawai Badan Keuangan dan Aset Daerah Kota Kupang - Djonu, Janny Haryati; Man, Stanis; Yasinto, Yulius; Niha, Simon Sia; Djuang, Gaudensius (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
The aim of this research is to determine the significance of the relationship between work motivation and employee work discipline; and to ensure the significance of the relationship between work motivation and compensation in terms of mediating the relationship between these influences in the Financial Agency and Regional Assets of Kupang City. This research uses quantitative techniques. Descriptive statistical analysis shows that motivating employees in the workplace is influenced positively and significantly by leadership, rewards and punishment. Discipline in the workplace is significantly and beneficially influenced by leadership, rewards, and punishment. Work motivation influences work discipline positively but not significantly. Workplace motivation is not a moderator of how leadership, rewards, and punishment influence workplace discipline.